1956
DOI: 10.1136/bmj.1.4979.1318
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Epithelial Cells in Ulcerative Colitis

Abstract: Sister Houle for her active co-operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

1957
1957
1978
1978

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 7 publications
2
5
1
Order By: Relevance
“…During the first and second days the cells that advance over the floor of a lesion are flattened in form before becoming hypertrophied, and this feature of regenerating epithelium is very well exemplified by most of the simple epithelia referred to here. Findings similar to those in experimental lesions are found in human pathological material; they are common in healing peptic ulcers and have been noted by Counsel1 (1955) in the ileum and Boddington & Truelove (1956) in the rectum during reparative phases in ulcerative colitis. Such an attempt to cover as much of a lesion as quickly as possible in the early stages of repair was regarded by earlier workers, e.g.…”
Section: ( I ) Epithelial Reactionssupporting
confidence: 77%
“…During the first and second days the cells that advance over the floor of a lesion are flattened in form before becoming hypertrophied, and this feature of regenerating epithelium is very well exemplified by most of the simple epithelia referred to here. Findings similar to those in experimental lesions are found in human pathological material; they are common in healing peptic ulcers and have been noted by Counsel1 (1955) in the ileum and Boddington & Truelove (1956) in the rectum during reparative phases in ulcerative colitis. Such an attempt to cover as much of a lesion as quickly as possible in the early stages of repair was regarded by earlier workers, e.g.…”
Section: ( I ) Epithelial Reactionssupporting
confidence: 77%
“…Therefore, care should be taken whenever cytological examination is performed in adnoma. In contrast, such very atypical cells as reported previously by Galambos et al (1956) and Boddington and Truelove (1956) appeared infrequently in ulcerative colitis in this series, while a great many of neutrophils together with multinucleated giant cells or plasma cells were characteristic of the active stage of ulcerative colitis (Watanabe et al 1977). Bemvenuti et al (1974) reported that 4 cases of cancer associated with ulcerative colitis were correctly diagnosed cytologically.…”
Section: Resultscontrasting
confidence: 48%
“…In a previous study (Boddington and Truelove, 1956) it was found that the colonic epithelial cells are frequently abnormal in ulcerative colitis. Compared with normal colonic epithelial cells, many of those seen in active ulcerative colitis are much enlarged, with big nuclei having nucleoli and a disturbed chromatin pattern.…”
Section: And 2 Cytological Findingsmentioning
confidence: 92%
“…from the anal margin, by means of an improved version of a special colonic biopsy instrument (Truelove et al, 1955). Specimens were taken for cytological examination by the Papanicolaou technique by means of a special instrument described previously (Boddington and Truelove, 1956).…”
Section: Present Investigationmentioning
confidence: 99%